Information and knowledge assessment – Results from a multinational automotive company. (October 2020) - Heisig, Peter; Ogaza, Martin A.; Hamraz, Bahram
Abstract: This article reports the results from an information and knowledge assessment (IKA) to identify information and knowledge needs and, their coverage by information resources to derive recommendations for improvement and proposes a contingeny framework. The approach is based on a review of audit methods from information sciences and management, knowledge management and the engineering discipline and tested with data (N = 580) collected from the engineering domain within an automotive supplier over six European sites. The integrated assessment uses content needs profiles from two complementary perspectives, the coverage of needs by various internal information sources and data on awareness and usage of these information sources. The employment of content categories on a more granular analytical level than information systems sources opens up new possibilities to derive improvement measures and requirements for the design of information systems within an organization. The brief data-gathering instrument also reduces the required resources to implement this approach considerably overcoming weaknesses previously identified in case studies and the IA literature. It makes a contribution to research bridging the gap between research and practice and opens up options to design contingency frameworks for a specific domain.